Relationship Between Supply Chain Management and Competitor Intensity in The Food Business: A Structural Equation Model - Karen Earnshaw (Journal of Economics Business Industry, 2023)
Supply Chain Management (S.C.M.) was developed as a system and coordination of strategies of business functions that manage supply chains to improve long-term performance. This study aims to analyze the relationship between the implementation of supply chain management and the intensity of competitors in the food business, analyze the relationship of competitor intensity to company performance, and provide recommendations on the Food and beverage business related to increasing competitiveness based on the implementation of supply chain management. The results showed that the implementation of supply chain management on competitor intensity has a significant relationship with an influence of 44.5%, and the relationship of competitor intensity to company performance is a meaningful relationship with a power of 65.2%. From the recommendations, food business people and innovative products are recommended to expand and cover the entire market by considering aspects of logistics distribution, digital marketing, and product gallery development